2021
DOI: 10.1159/000515138
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Acupuncture for Herpes Zoster: A Systematic Review and Meta-Analysis

Abstract: <b><i>Introduction:</i></b> This study aimed to assess the efficacy of acupuncture in patients with herpes zoster (HZ) based on current randomized clinical trials (RCTs). <b><i>Methods:</i></b> Five databases were screened for RCTs published until August 2019. Studies that assessed the efficacy of acupuncture when used as an independent intervention for HZ were included. The outcomes of interest were pain intensity, as assessed using the visual analog scale (VAS)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(26 citation statements)
references
References 17 publications
0
26
0
Order By: Relevance
“…According to the retrieval strategy, a total of 77 related articles were selected, 36 duplicates were removed, 3 studies were excluded after record screening, and 19 studies were included (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The entire process and results are shown in Figure 1.…”
Section: Results Of the Literature Search And Selection Processmentioning
confidence: 99%
See 1 more Smart Citation
“…According to the retrieval strategy, a total of 77 related articles were selected, 36 duplicates were removed, 3 studies were excluded after record screening, and 19 studies were included (13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31). The entire process and results are shown in Figure 1.…”
Section: Results Of the Literature Search And Selection Processmentioning
confidence: 99%
“…The 318 included studies involved 13490 cases. Among them, 3 articles (14-16) included RCTs and CCTs, and 16 articles (13,(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31) were RCTs. Thirteen articles (13,15,18,19,(21)(22)(23)(25)(26)(27)(28)(29)(30)(31) used the bias risk assessment tool recommended by Cochrane.…”
Section: Description Of the Included Reviewsmentioning
confidence: 99%
“…These methods were not the only ones that physicians also made determinations based on their clinical experience. With the deepening of clinical research, the efficacy of acupuncture on neuropathic pain has been confirmed by several systemic reviews and meta-analyses, which were listed in Table 2 ( Heo et al, 2013 ; Dimitrova et al, 2017 ; Hu et al, 2019 ; Liu et al, 2019 ; Pei et al, 2019 ; Yun et al, 2020 ; Cui et al, 2021 ; Yu et al, 2021 ). A study described the effectiveness and safety of acupuncture for the treatment of chemotherapy-induced peripheral neuropathy.…”
Section: Application Of Acupuncture For Neuropathic Painmentioning
confidence: 93%
“…Wet cupping [30] , Longdancao (Gentiana scabra Bunge. )single herb formula [31] and acupuncture [32] may decrease the rate of PHN. Acupuncture using independently [31] and Acupuncture plus moxibustion [33] may reduce VAS score of pain.…”
Section: Comparison With Other Studiesmentioning
confidence: 98%